Electrolyte, battery, preparation method thereof, and electrical equipment
By adding magnetic nanoparticles and their functional modification layer to the electrolyte of the lithium-ion battery, the problem of insufficient diffusion rate of lithium ions is solved, and the effect of reducing the internal resistance of the battery and improving the cycle life and fast charging performance is achieved.
Patent Information
- Application Number
- CN202411068997.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-06
AI Technical Summary
Due to the diffusion rate limit of lithium ions in the electrolyte, lithium ion batteries have large internal resistance and short cycle life, which cannot meet the needs of high power density and fast charging.
Magnetic additives, including magnetic nanoparticles and their functional modification layers on the surface, are introduced into the electrolyte, to improve the diffusion rate of lithium ions and the wetting ability of the electrolyte.
By introducing magnetic additives, the internal resistance of the battery is reduced, the cycle life and fast charging performance of the battery are improved, and the infiltration capacity and ion transmission rate of the electrolyte are enhanced.
Smart Images

Figure CN118659034B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to an electrolyte, a battery, a preparation method thereof, and electrical equipment. Background Art
[0002] In electrochemical systems such as lithium-ion batteries, the movement of active ions (such as lithium ions) in the electrolyte is crucial for ion transport and reaction rates, which in turn affects the battery's impedance and cycle life. Currently, due to factors such as the diffusion rate of active ions in the electrolyte, batteries generally have problems such as large internal resistance and short cycle life, which need to be solved urgently. For example, in lithium-ion batteries, lithium ions in the electrolyte form solvated lithium with solvent molecules, and the solvated lithium diffuses in the liquid phase driven by potential difference and concentration difference. With the rapid development of electric vehicles, portable electronic devices, and energy storage systems, the requirements for battery performance such as power density and charging rate are getting higher and higher. However, lithium-ion batteries are limited by factors such as the diffusion rate of lithium ions in the electrolyte, which makes lithium-ion batteries generally have defects such as large internal resistance. Summary of the invention
[0003] The present invention provides an electrolyte, a battery and a preparation method thereof, and an electrical device, which can reduce the internal resistance of the battery, improve the cycle life of the battery and other performances, and effectively overcome the defects of the prior art.
[0004] One aspect of the present invention provides an electrolyte comprising a magnetic additive, wherein the magnetic additive comprises magnetic nanoparticles.
[0005] According to one embodiment of the present invention, the magnetic additive further comprises a functional modification layer present on the surface of the magnetic nanoparticles, and the functional modification layer comprises an organic matrix material containing oxygen and / or nitrogen elements.
[0006] According to one embodiment of the present invention, the organic matrix material contains one or more of a carboxyl group, an ether group, a carbonyl group, an amino group, and a pyridyl group.
[0007] According to one embodiment of the present invention, the thickness of the functional modification layer is 2 nm to 10 nm.
[0008] According to one embodiment of the present invention, the magnetic nanoparticles include one or more of magnetic metal oxide nanoparticles, metal nanoparticles, and alloy nanoparticles.
[0009] According to one embodiment of the present invention, the magnetic metal oxide nanoparticles include ferroferric oxide nanoparticles, the metal nanoparticles include one or more of cobalt nanoparticles, nickel nanoparticles and iron nanoparticles, and the alloy nanoparticles include iron-cobalt alloy nanoparticles and / or iron-nickel alloy nanoparticles.
[0010] According to one embodiment of the present invention, the mass percentage of the magnetic additive in the electrolyte is 0.01%~3%.
[0011] According to one embodiment of the present invention, the electrolyte further includes a first solvent, the first solvent includes an organic solvent, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate; and / or, the electrolyte further includes a lithium salt, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(fluorosulfonyl)imide.
[0012] Another aspect of the present invention provides a method for preparing the above electrolyte, comprising the following steps: mixing the magnetic additive, a first solvent, and an electrolyte salt to obtain the electrolyte.
[0013] According to one embodiment of the present invention, the mixing of the magnetic additive, the first solvent, and the electrolyte salt to obtain the electrolyte specifically comprises: mixing the magnetic additive, the first solvent, and the electrolyte salt, and stirring for 2h to 8h to obtain the electrolyte.
[0014] According to one embodiment of the present invention, the preparation process of the magnetic additive includes: using a first silane coupling agent containing oxygen and / or nitrogen elements to perform a first silane modification treatment on magnetic nanoparticles to form a functionalized modification layer on the surface of the magnetic nanoparticles to obtain the magnetic additive.
[0015] According to one embodiment of the present invention, the temperature of the first silane modification treatment is 25°C~80°C, and the time is 6h~12h; and / or, the first silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethylsilane, 3-aminopropyltriethylsilane, and (3-trimethoxysilylpropyl)-4-pyridine.
[0016] According to one embodiment of the present invention, the preparation process of the magnetic additive includes: using a second silane coupling agent to perform a second silane modification treatment on magnetic nanoparticles to obtain silane-modified magnetic nanoparticles; reacting the silane-modified magnetic nanoparticles with a functional modifier to form a functionalized modification layer on the surface of the magnetic nanoparticles to obtain the magnetic additive; wherein at least one of the second silane coupling agent and the functional modifier includes an organic compound containing oxygen and / or nitrogen elements.
[0017] According to one embodiment of the present invention, the temperature of the second silane modification treatment is 25°C~80°C, and the time is 6h~12h; and / or, the conditions for the reaction of the silane-modified magnetic nanoparticles and the functional modifier are: the reaction temperature is 25°C~80°C, and the reaction time is 3h~12h; and / or, the functional modifier includes one or more of succinic anhydride, ethylene oxide, trimethylacetyl chloride, and pyridine; and / or, the second silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, (3-chloropropyl)trimethoxysilane, (3-iodopropyl)trimethoxysilane, trichlorosilane, 3-aminopropyltrimethylsilane, and 3-aminopropyltriethylsilane.
[0018] Another aspect of the present invention provides a battery, comprising a positive electrode sheet, a separator, a negative electrode sheet, and the above electrolyte or an electrolyte prepared according to the above electrolyte preparation method.
[0019] According to one embodiment of the present invention, the battery is a lithium-ion battery.
[0020] Another aspect of the present invention provides a method for preparing a battery, comprising the following steps: placing a battery cell in a shell, adding an electrolyte thereto, to obtain a battery precursor; placing the battery precursor in a magnetic field for magnetic field induction treatment, to obtain the battery; wherein the battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet, and the electrolyte comprises the above-mentioned electrolyte or an electrolyte prepared according to the above-mentioned electrolyte preparation method.
[0021] According to one embodiment of the present invention, the magnetic field strength of the magnetic field is 0.1T~0.5T; and / or the magnetic field direction of the magnetic field is parallel to the thickness direction of the battery core; and / or the battery preparation method also includes a process of aging, forming and aging the battery precursor, and the aging, forming and aging processes are performed during the process of placing the battery precursor in a magnetic field for magnetic field induction treatment.
[0022] Another aspect of the present invention provides an electrical device, comprising the above-mentioned battery or a battery manufactured according to the above-mentioned battery manufacturing method.
[0023] According to one embodiment of the present invention, the electrical device further comprises a second magnetic field device for applying a magnetic field to the battery.
[0024] The electrolyte, battery, preparation method thereof and electrical equipment provided by the present invention introduce a magnetic additive into the electrolyte, which can increase the diffusion rate of active ions (such as lithium ions in lithium-ion batteries) in the electrolyte and the wetting ability of the electrolyte on the battery core, thereby reducing the internal resistance of the battery, improving the fast charging and low-temperature charging and discharging performance of the battery, and at the same time improving the cycle life and other performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of a magnetic additive according to an embodiment of the present invention.
[0026] Explanation of reference numerals: 1: magnetic nanoparticles; 2: functionalized modification layer. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0028] The embodiment of the present invention provides an electrolyte, such as Figure 1 As shown, the electrolyte includes a magnetic additive, and the magnetic additive includes magnetic nanoparticles 1.
[0029] The electrolyte of the embodiment of the present invention is a magnetic nanofluid electrolyte, in which the magnetic additive can interact with the active ions in the electrolyte, indirectly giving the active ions magnetic properties, thereby increasing the diffusion rate of lithium ions in the electrolyte and the wetting ability of the electrolyte to the battery cell. At the same time, an external magnetic field can be used to achieve precise control of the diffusion of active ions. Compared with the driving mode (electric field drive and concentration gradient drive) generated by the electrochemical reaction based on the potential difference between the positive and negative electrodes, it is more controllable and flexible, and can increase the transmission rate of active ions in the electrolyte, reduce the internal resistance of the battery, and improve the battery's cycle life and other performance.
[0030] According to further research by the inventors, Figure 1As shown, the magnetic additive may further include a functionalized modification layer 2 present on the surface of the magnetic nanoparticle 1, and the functionalized modification layer 2 includes an organic matrix material containing oxygen (O) and / or nitrogen (N), which is beneficial to further reduce the battery impedance, improve the battery's fast charging and low-temperature charging and discharging performance, and improve the battery's cycle life and other performance. The reason for this is that in the magnetic additive, the surface of the magnetic nanoparticle 1 has an organic matrix material containing oxygen and / or nitrogen, which can improve the dispersibility of the magnetic additive in the electrolyte, and can coordinate with the active ions in the electrolyte (such as lithium ions in lithium-ion batteries) to form a solvated structure with magnetism (i.e., solvated ions (such as solvated lithium ions)), thereby playing the role of a carrier and conductive ion in the battery, improving the diffusion rate of lithium ions in the electrolyte and the electrolyte's wetting ability to the battery core, and at the same time, the flow of the electrolyte can be regulated by an external magnetic field driving force, the electrolyte's wetting ability and ion transmission rate can be enhanced, the battery's internal resistance can be reduced, the battery charging rate can be increased, and the battery's cycle life and other performance can be improved.
[0031] Further research has shown that the organic matrix material may contain one or more of a carboxyl group, an ether group, a carbonyl group, an amino group, and a pyridine group, so that the organic matrix material contains oxygen and / or nitrogen elements. By using an organic matrix material having at least one of these groups to form a functionalized modified layer 2, it is beneficial to improve the cycle life of the battery while reducing the internal resistance of the battery. The reason for this is that when the functionalized modified layer 2 includes an organic matrix material containing at least one of these groups, it is beneficial to improve the dispersibility of the magnetic additive in the electrolyte, and at the same time, it is easy for the magnetic additive to coordinate with active ions such as lithium ions, thereby improving the ion transfer rate of the electrolyte and the wetting ability of the battery cell, reducing the internal resistance of the battery, and improving the cycle life of the battery.
[0032] Specifically, the functional modification layer may include one or more of a first silane coupling agent grafted onto the surface of the magnetic nanoparticles and a reaction product of a second silane coupling agent and a functional modification agent.
[0033] When the functional modification layer includes a first silane coupling agent grafted on the surface of the magnetic nanoparticles, the first silane coupling agent contains oxygen and / or nitrogen elements, and specifically may contain one or more of carboxyl groups, ether groups, carbonyl groups, amino groups, and pyridyl groups, so that the organic matrix material of the formed functional modification layer contains oxygen and / or nitrogen elements, and specifically may contain one or more of carboxyl groups, ether groups, carbonyl groups, amino groups, and pyridyl groups.
[0034] Exemplarily, the organic matrix material of the functionalized modification layer contains amino groups, and the first silane coupling agent used includes a silane compound containing amino groups, specifically including one or more of 3-aminopropyltriethoxysilane (APTES), 3-aminopropyltrimethylsilane, and 3-aminopropyltriethylsilane.
[0035] Exemplarily, the organic matrix material of the functionalized modification layer contains a pyridine group, and the first silane coupling agent used includes a silane compound containing a pyridine group, and specifically may include (3-trimethoxysilylpropyl)-4-pyridine.
[0036] In some embodiments, the first silane coupling agent may include one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethylsilane, 3-aminopropyltriethylsilane, and (3-trimethoxysilylpropyl)-4-pyridine.
[0037] In some embodiments, the magnetic additive can be prepared according to a process including the following steps: using a first silane coupling agent to perform a first silane modification treatment on magnetic nanoparticles to form a functionalized modification layer on the surface of the magnetic nanoparticles (i.e., reacting the magnetic nanoparticles with the first silane coupling agent to graft the first silane coupling agent on the surface thereof to form a functionalized modification layer), to obtain the magnetic additive. The temperature of the first silane modification treatment can be 25°C to 80°C, and the time can be 6h to 12h.
[0038] When the functional modification layer includes the reaction product of the second silane coupling agent grafted on the surface of the magnetic nanoparticles and the functional modifier, at least one of the second silane coupling agent and the functional modifier contains oxygen and / or nitrogen. Specifically, at least one of the second silane coupling agent and the functional modifier includes an organic compound containing oxygen and / or nitrogen, so that the reaction product of the second silane coupling agent grafted on the surface of the magnetic nanoparticles and the functional modifier contains oxygen and / or nitrogen, specifically, it can contain one or more of carboxyl, ether, carbonyl, amino, and pyridyl, and then the organic matrix material of the formed functional modification layer contains oxygen and / or nitrogen, specifically, it can contain one or more of carboxyl, ether, carbonyl, amino, and pyridyl.
[0039] For example, the second silane coupling agent may contain oxygen and / or nitrogen, while the functional modifier may not contain oxygen and / or nitrogen; or the second silane coupling agent may not contain oxygen and / or nitrogen, while the functional modifier may contain oxygen and / or nitrogen; or the second silane coupling agent may contain oxygen and / or nitrogen, while the functional modifier may also contain oxygen and / or nitrogen.
[0040] In some embodiments, the magnetic additive can be prepared according to a process including the following steps: using a second silane coupling agent to perform a second silane modification treatment on magnetic nanoparticles to obtain silane-modified magnetic nanoparticles; reacting the silane-modified magnetic nanoparticles with a functional modifier to form a functionalized modification layer on the surface of the magnetic nanoparticles to obtain the magnetic additive. In the preparation process, the magnetic nanoparticles are first reacted with the second silane coupling agent to graft the second silane coupling agent on the surface to obtain the silane-modified magnetic nanoparticles; then the silane-modified magnetic nanoparticles are reacted with the functional modifier, and during the reaction, the second silane coupling agent grafted on the surface of the magnetic nanoparticles reacts with the functional modifier to generate a reaction product of the second silane coupling agent grafted on the surface of the magnetic nanoparticles and the functional modifier, thereby forming a functionalized modification layer on the surface of the magnetic nanoparticles to obtain the magnetic additive.
[0041] The temperature of the second silane modification treatment may be 25° C. to 80° C., and the time may be 6 h to 12 h.
[0042] The conditions for the reaction of the silane-modified magnetic nanoparticles and the functional modifier are as follows: the reaction temperature is 25° C. to 80° C., and the reaction time can be 3 h to 12 h.
[0043] Specifically, the functional modifier includes an organic compound, which may include one or more of anhydride compounds, epoxy compounds, acyl halide compounds, and pyridine compounds. Among them, the anhydride compound may include succinic anhydride; the epoxy compound may include oxirane compounds, specifically ethylene oxide; the halogen in the acyl halide compound may include one or more of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I); the acyl halide compound may include trimethylacetyl halide, specifically trimethylacetyl chloride; the pyridine compound may include pyridine.
[0044] In some embodiments, the functional modifier may include one or more of succinic anhydride, ethylene oxide, and trimethylacetyl pyridine chloride, which is beneficial to reduce the internal resistance of the battery and improve the cycle life of the battery.
[0045] In addition, the second silane coupling agent may include an amino group-containing silane compound and / or a halogen-containing silane compound, and the halogen in the halogen-containing silane compound may include one or more of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I).
[0046] Specifically, the amino group-containing silane compound may include one or more of APTES, 3-aminopropyltrimethylsilane, and 3-aminopropyltriethylsilane.
[0047] Specifically, the halogen-containing silane compound may include one or more of (3-chloropropyl)trimethoxysilane, (3-iodopropyl)trimethoxysilane (IPTMS), and trichlorosilane.
[0048] In some embodiments, the second silane coupling agent may include one or more of 3-aminopropyltriethoxysilane (APTES), (3-chloropropyl)trimethoxysilane, (3-iodopropyl)trimethoxysilane (IPTMS), trichlorosilane, 3-aminopropyltrimethylsilane, and 3-aminopropyltriethylsilane.
[0049] Exemplarily, the functional modification agent includes anhydride compounds, and the anhydride compounds (such as succinic anhydride) can react with amino-containing silane compounds (such as APTES) to generate reaction products containing carboxyl groups (-COOH), thereby introducing carboxyl groups into the formed functional modification layer.
[0050] Exemplarily, the functional modification agent includes epoxy compounds, and epoxy compounds (such as ethylene oxide) can react with halogen-containing silane compounds (such as (3-chloropropyl)trimethoxysilane). During the reaction, the epoxy compound undergoes a ring-opening reaction and reacts with (3-chloropropyl)trimethoxysilane to generate a reaction product containing an ether group, thereby introducing an ether group into the formed functional modification layer.
[0051] Exemplarily, the functionalized modifier includes an acyl halide compound, and the acyl halide compound (such as trimethylacetyl chloride) can react with a silane compound containing an amino group (such as APTES) to remove HX (X represents a halogen) to generate a reaction product containing a carbonyl group, thereby introducing a carbonyl group into the formed functionalized modified layer. Taking trimethylacetyl chloride and APTES as an example, in the preparation process of the magnetic additive, APTES and magnetic nanoparticles are first reacted (i.e., the second silane modification treatment), APTES is grafted on the surface of the magnetic nanoparticles, and amino groups are introduced into the magnetic nanoparticles, and then reacted with trimethylacetyl chloride, and the carbonyl carbon atom in the trimethylacetyl chloride reacts with the nitrogen atom in the amino group to remove HX (X represents a halogen), thereby generating a reaction product containing a carbonyl group.
[0052] Exemplarily, the functional modification agent includes a pyridine compound, and the pyridine compound (such as pyridine) can react with a halogen-containing silane compound (such as (3-chloropropyl)trimethoxysilane) to generate a reaction product containing a pyridine group, thereby introducing a pyridine group into the formed functional modification layer.
[0053] In addition, in the above-mentioned magnetic additive, the thickness of the functionalized modification layer can be 2nm~10nm, for example, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm or a range composed of any two of them, which is beneficial to reduce the internal resistance of the battery and improve the cycle life and other performance of the battery. At the same time, considering factors such as the active sites on the surface of the magnetic nanoparticles 1 that can attach to the organic matrix material, by controlling the thickness of the functionalized modification layer within the above-mentioned range (2nm~10nm), it is also beneficial to the preparation of the magnetic additive.
[0054] Specifically, the magnetic nanoparticles 1 may include one or more of magnetic metal oxide nanoparticles, metal nanoparticles, and alloy nanoparticles, which are beneficial to reducing the internal resistance of the battery and improving the cycle life of the battery.
[0055] In some embodiments, the magnetic metal oxide nanoparticles may include ferrosoferric oxide (Fe 3 O 4 ) nanoparticles.
[0056] In some embodiments, the metal nanoparticles may include one or more of cobalt nanoparticles, nickel nanoparticles, and iron nanoparticles.
[0057] In some embodiments, the alloy nanoparticles may include iron-cobalt alloy nanoparticles (iron-cobalt alloy nanoparticles) and / or iron-nickel alloy nanoparticles (iron-nickel alloy nanoparticles).
[0058] According to further research by the inventors, the mass percentage of the magnetic additive in the electrolyte (i.e., the proportion of the mass of the magnetic additive to the total mass of the electrolyte) can be 0.01% to 3%, for example, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range composed of any two of them. In this way, the electrolyte can contain more magnetic additives, thereby reducing the internal resistance of the battery and improving the cycle life of the battery. At the same time, it is beneficial for the electrolyte to have suitable properties such as viscosity, improve the wettability of the electrolyte to the battery cell, and further reduce the internal resistance of the battery and improve the cycle life of the battery.
[0059] Generally, the electrolyte also includes a first solvent and an electrolyte salt. The concentration of the electrolyte salt in the electrolyte can be 0.5 mol / L~3 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L or a range consisting of any two of them.
[0060] In an embodiment of the present invention, the electrolyte may be a non-aqueous electrolyte, the first solvent includes an organic solvent, and the organic solvent may include one or more of ethylene carbonate (EC), propylene carbonate, diethyl carbonate, dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). By adopting the organic solvent, it is beneficial to adapt to the above-mentioned magnetic additives, improve the wetting ability and ion diffusion rate of the electrolyte, reduce the internal resistance of the battery, and improve the cycle life and other performance of the battery.
[0061] Specifically, the above-mentioned electrolyte salt may include a lithium salt, and the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate, and lithium bis(fluorosulfonyl)imide, which is conducive to adapting to the above-mentioned magnetic additives, improving the wetting ability and ion diffusion rate of the electrolyte, reducing the internal resistance of the battery, and improving the cycle life of the battery and other performance.
[0062] The embodiment of the present invention further provides a method for preparing the above electrolyte, comprising the following steps: mixing a magnetic additive, a first solvent, and an electrolyte salt to obtain an electrolyte.
[0063] In some embodiments, the magnetic additive, the first solvent, and the electrolyte salt are mixed to obtain an electrolyte, specifically comprising: mixing the magnetic additive, the first solvent, and the electrolyte salt, and stirring for 2 h to 8 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, or a range of any two thereof, to obtain an electrolyte. Wherein, the stirring time is within the range of 2 h to 8 h, which can improve the dispersibility of the magnetic additive in the electrolyte, further reduce the internal resistance of the battery, improve the cycle life of the battery and other performance, and at the same time avoid the stirring time being too long and affecting the preparation efficiency of the electrolyte.
[0064] In addition, the preparation method of the electrolyte also includes a preparation process of a magnetic additive.
[0065] As mentioned above, in some embodiments, the preparation process of the magnetic additive may include: using a first silane coupling agent containing oxygen and / or nitrogen elements to perform a first silane modification treatment on the magnetic nanoparticles to form a functionalized modification layer on the surface of the magnetic nanoparticles to obtain a magnetic additive.
[0066] Among them, the temperature of the first silane modification treatment can be 25°C~80°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range composed of any two of them, which is conducive to forming a functionalized modification layer, improving the performance preparation efficiency of the magnetic additive, and reducing energy consumption.
[0067] In addition, the time of the first silane modification treatment can be 6h~12h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range composed of any two of them, which is conducive to forming a functionalized modification layer and improving the performance and preparation efficiency of the magnetic additive.
[0068] In addition, the first silane modification treatment can be carried out in a second solvent, and the second solvent may include an organic solvent and water, that is, the second solvent may be a mixed solvent containing an organic solvent and water. In such a mixed solvent system, the first silane coupling agent is facilitated to hydrolyze, thereby being grafted on the surface of the magnetic nanoparticles, forming a functionalized modification layer on the surface of the magnetic nanoparticles, and preparing a magnetic additive.
[0069] Specifically, the organic solvent used as the second solvent may include an alcohol solvent, that is, the second solvent may include an alcohol solvent and water, and the alcohol solvent may specifically include ethanol.
[0070] In some embodiments, the second solvent includes ethanol and water, that is, a mixed solvent containing ethanol and water is used as the second solvent, which is beneficial to improving the preparation efficiency and performance of the magnetic additive.
[0071] Specifically, in the second solvent, the volume ratio of water to the organic solvent can be 1:(0.5-2), for example, 1:0.5, 1:0.8, 1:1, 1:1.3, 1:1.5, 1:1.8, 1:2 or a range consisting of any two of them.
[0072] Specifically, the first silane modification treatment may be performed under an inert atmosphere, and the inert atmosphere includes, for example, a nitrogen atmosphere and / or an argon atmosphere, etc., and is not particularly limited thereto.
[0073] In a specific implementation, the magnetic nanoparticles can be dispersed in a second solvent under an inert atmosphere, and then the first silane coupling agent is added thereto for reaction (i.e., first silane modification treatment). After the reaction is completed, the unreacted first silane coupling agent (silanization agent) is removed by centrifugation and washing to obtain a magnetic additive.
[0074] In other embodiments, the preparation process of the magnetic additive may include: performing a second silane modification treatment on magnetic nanoparticles using a second silane coupling agent to obtain silane-modified magnetic nanoparticles; reacting the silane-modified magnetic nanoparticles with a functional modifier to form a functionalized modification layer on the surface of the magnetic nanoparticles; wherein at least one of the second silane coupling agent and the functional modifier includes an organic compound containing oxygen and / or nitrogen elements.
[0075] In the preparation process of the above-mentioned magnetic additive, the magnetic nanoparticles are coupled with a silane coupling agent through a second silane modification treatment, that is, the second silane coupling agent is grafted on the surface of the magnetic nanoparticles (that is, the silane-modified magnetic nanoparticles are mainly formed by magnetic nanoparticles and the second silane coupling agent grafted on the magnetic nanoparticles). Subsequently, in the process of reacting it with a functional modifier, the functional modifier and the second silane coupling agent in the silane-modified magnetic nanoparticles are coupled, so that the functional modifier wraps the magnetic nanoparticles through the second silane coupling agent, thereby forming a functionalized modification layer on the surface of the magnetic nanoparticles to prepare the magnetic additive.
[0076] In addition, the second silane modification treatment can be carried out in a third solvent, and the third solvent includes an organic solvent and water, that is, the third solvent can be a mixed solvent containing an organic solvent and water. In such a mixed solvent system, the second silane coupling agent is facilitated to hydrolyze, thereby being grafted on the surface of the magnetic nanoparticles. Combined with the subsequent functional modification process (i.e., the process of reaction between silane-modified magnetic nanoparticles and functional modifiers), a functional modification layer is formed on the surface of the magnetic nanoparticles to obtain a magnetic additive.
[0077] Specifically, the organic solvent used as the third solvent may include an alcohol solvent, that is, the third solvent may include an alcohol solvent and water, and the alcohol solvent may specifically include ethanol.
[0078] In some embodiments, the third solvent includes ethanol and water, that is, a mixed solvent containing ethanol and water is used as the third solvent, which is beneficial to improving the preparation efficiency and performance of the magnetic additive.
[0079] Specifically, in the third solvent, the volume ratio of water to the organic solvent can be 1:(0.5-2), for example, 1:0.5, 1:0.8, 1:1, 1:1.3, 1:1.5, 1:1.8, 1:2 or a range consisting of any two of them.
[0080] Specifically, the silane modification treatment may be performed under an inert atmosphere, and the inert atmosphere includes, for example, a nitrogen atmosphere and / or an argon atmosphere, etc., which is not particularly limited.
[0081] Specifically, the temperature of the second silane modification treatment can be 25°C~80°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range composed of any two of them, which is conducive to forming a functionalized modification layer, improving the performance and preparation efficiency of the magnetic additive, and reducing energy consumption.
[0082] In addition, the time of the second silane modification treatment can be 6h~12h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range composed of any two of them, which is conducive to forming a functionalized modification layer and improving the performance and preparation efficiency of the magnetic additive.
[0083] In addition, the above-mentioned process of reacting silane-modified magnetic nanoparticles and functional modifiers can be carried out in a fourth solvent, and the fourth solvent includes an organic solvent, which may include one or more of toluene, ethanol, dichloromethane, and tetrahydrofuran (THF), wherein the ethanol used can specifically be anhydrous ethanol.
[0084] Specifically, the process of reacting the silane-modified magnetic nanoparticles with the functional modifier can be carried out under an inert atmosphere, and the inert atmosphere includes, for example, a nitrogen atmosphere and / or an argon atmosphere, etc., and is not particularly limited thereto.
[0085] Specifically, the reaction temperature of the silane-modified magnetic nanoparticles and the functional modifier can be 25°C to 80°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range composed of any two of them, which is conducive to forming a functionalized modification layer, improving the performance and preparation efficiency of the magnetic additive, and reducing energy consumption.
[0086] In addition, the reaction time of the silane-modified magnetic nanoparticles and the functional modifier is 3 h to 12 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or a range composed of any two of them, which is conducive to forming a functionalized modification layer and improving the performance and preparation efficiency of the magnetic additive.
[0087] In a specific implementation, the magnetic nanoparticles can be dispersed in a third solvent under an inert atmosphere, and then a second silane coupling agent is added thereto for reaction (i.e., second silane modification treatment). After the reaction is completed, the unreacted second silane coupling agent (silanization agent) is removed by centrifugation and washing to obtain silane-modified magnetic nanoparticles. Subsequently, the silane-modified magnetic nanoparticles (i.e., surface-treated magnetic nanoparticles) and the functional modifier can be dispersed in a fourth solvent and reacted under an inert atmosphere to obtain a magnetic additive (i.e., magnetic nanoparticles having a functionalized modification layer on the surface).
[0088] In the process of preparing the magnetic additive, the first silane coupling agent, the second silane coupling agent, the functional modifier and other materials used are described in the above content and will not be described in detail here.
[0089] In an embodiment of the present invention, magnetic nanoparticles can be obtained by conventional methods in the art, for example, they can be purchased commercially or prepared by conventional methods in the art. For example, Fe3O4 nanoparticles can be prepared by the reaction of ferric iron salts and divalent iron salts. The reaction of ferric iron salts and divalent iron salts can generally be carried out under alkaline conditions, and specifically, alkaline conditions can be provided by alkaline compounds such as ammonia water; wherein ferric iron salts include water-soluble ferric iron salts, specifically ferric chloride (FeCl3), and divalent iron salts include water-soluble divalent iron salts, specifically ferric dichloride (FeCl2). In specific implementation, hydrates of ferric chloride (such as FeCl3.6H2O) and hydrates of ferric dichloride (such as FeCl2.4H2O) can be used to prepare Fe3O4 nanoparticles.
[0090] In some embodiments, the preparation process of Fe3O4 nanoparticles may include: dissolving trivalent iron salt and divalent iron salt in water under an inert atmosphere, adding an aqueous ammonia solution thereto to provide alkaline conditions, and reacting under alkaline conditions to obtain Fe3O4 nanoparticles. After the reaction is completed, purification may be performed by magnetic separation, washing, drying, etc. to obtain Fe3O4 nanoparticles.
[0091] In a specific implementation, FeCl3.6H2O and FeCl2.4H2O can be dissolved in 100 mL of water at a molar ratio of 2:1 under an inert atmosphere, and an ammonia solution is slowly added until the pH value of the solution is about 10. After reacting for 3 hours, magnetic separation is performed, and then washing and drying are performed to synthesize Fe3O4 nanoparticles.
[0092] An embodiment of the present invention further provides a battery, comprising the above electrolyte or the electrolyte prepared according to the above electrolyte preparation method. The battery has the advantages corresponding to the above electrolyte, which will not be described in detail.
[0093] The battery in the embodiment of the present invention may be a lithium-ion battery (such as a lithium-ion power battery), a solar cell, or other new energy storage batteries.
[0094] For batteries (such as lithium-ion batteries) that drive the diffusion of active ions based on the electrochemical reaction caused by the potential difference between the positive and negative electrodes, the main ways to drive the diffusion of active ions are electric field drive and concentration gradient drive. Specifically, there is a potential difference between the positive and negative electrodes, and the positive and negative electrode materials undergo an electrochemical reaction. The generated electric field drives the diffusion of active ions such as lithium ions. At the same time, the electrode surface reacts faster, resulting in a relatively low concentration of active ions in the area close to the electrode surface, while a relatively high concentration of active ions in the area far from the electrode surface, thereby causing the active ions to move (diffuse) in the direction close to the electrode. In the embodiment of the present invention, by introducing an electrolyte containing the above-mentioned magnetic additive into such a battery (such as a lithium-ion battery), the magnetic properties of active ions such as lithium ions are indirectly given, which can improve the diffusion rate of active ions in the electrolyte and the wetting ability of the electrolyte to the battery core. At the same time, an external magnetic field (for example, a magnetic field is applied during the preparation of the battery and / or a magnetic field is applied during the use of the battery) can be used to achieve precise control of the diffusion of active ions such as lithium ions. Compared with the driving mode generated by the electrochemical reaction based on the potential difference between the positive and negative electrodes (battery driving and concentration gradient driving, etc.), the driving by an external electric field is more controllable and flexible, which can improve the controllability and flexibility of the battery preparation and use process, and can increase the transmission rate of active ions in the electrolyte, reduce the internal resistance of the battery, improve the fast charging performance of the battery, and improve the cycle life and other properties of the battery.
[0095] Generally, a battery includes a cell and a shell that encapsulates the cell. The electrolyte is injected into the cell in the shell. The cell includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet. The cell can be a laminated cell, that is, the cell is formed by alternating positive electrode sheets, separators, and negative electrode sheets.
[0096] Specifically, the positive electrode sheet includes a positive electrode collector and a positive electrode coating located on at least one side surface of the positive electrode collector. Specifically, the positive electrode coating can be provided on one side surface of the positive electrode collector, or the positive electrode coating can be provided on both sides of the positive electrode collector in the thickness direction.
[0097] Specifically, the positive electrode coating (positive electrode active material layer) may include a positive electrode active material, a conductive agent and a binder, all of which may be conventional materials in the art. For example, the positive electrode active material may include one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and a positive electrode ternary material. The positive electrode ternary material may include a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material. The conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fibers; the binder may include one or more of polyvinylidene fluoride (PVDF), polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, and the like.
[0098] The embodiment of the present invention may adopt a conventional positive electrode current collector in the art, for example, the positive electrode current collector includes copper foil.
[0099] In the embodiment of the present invention, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the components used to form the positive electrode coating, such as the positive electrode active material, the conductive agent, and the binder, can be dispersed in a fourth solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry, which is then coated on the surface of the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is prepared. Among them, the coating, drying, rolling and other processes involved are conventional operations for preparing positive electrode sheets by coating, and there is no special limitation on this.
[0100] Specifically, the negative electrode sheet includes a negative electrode collector and a negative electrode coating located on at least one side surface of the negative electrode collector. Specifically, the negative electrode coating can be provided on one side surface of the negative electrode collector, or the negative electrode coating can be provided on both sides of the negative electrode collector in the thickness direction.
[0101] Specifically, the negative electrode coating (negative electrode active material layer) may include a negative electrode active material, a conductive agent and a binder, all of which may be conventional materials in the art. For example, the negative electrode active material may include graphite, the conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fibers; the binder may include one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0102] The embodiment of the present invention may use a conventional negative electrode current collector in the art, for example, the negative electrode current collector includes copper foil.
[0103] In the embodiment of the present invention, the negative electrode sheet can be prepared by conventional methods in the art, for example, by coating. Specifically, the components for forming the negative electrode coating, such as the negative electrode active material, the conductive agent, and the binder, can be dispersed in a fifth solvent, such as water, to prepare a negative electrode slurry, which is then coated on the surface of the negative electrode collector, and after drying, rolling, and other processes, the negative electrode sheet is prepared. Among them, the coating, drying, rolling, and other processes involved are conventional operations for preparing negative electrode sheets by coating, and are not particularly limited thereto.
[0104] In the embodiment of the present invention, the separator is used to separate the positive electrode sheet and the negative electrode sheet to avoid short circuit between the positive electrode sheet and the negative electrode sheet. The embodiment of the present invention can adopt conventional separators in the art, for example, the separator includes a polypropylene film (PP film), but is not limited thereto.
[0105] In the embodiment of the present invention, the battery cell may be packaged with conventional shell materials in the art, and the shell may include, for example, soft packaging materials such as aluminum-plastic film (the battery in this case is a soft-package battery), but is not limited thereto.
[0106] The embodiments of the present invention can reduce the internal resistance of the battery and improve the cycle life and other performance of the battery, which can be specifically manifested in that the 50% SOC charging DC resistance (DCIR) of the battery is lower than (less than or equal to) 52.5%, further lower than 50%, further lower than 45%, and the capacity retention rate of the battery after 800 cycles at 0.5C at room temperature (about 25°C) is higher than (greater than or equal to) 91%, further higher than 92%, further higher than 93%, and further higher than 94%. Among them, the test process of the 50% SOC charging DC resistance of the battery and the test process of the capacity retention rate of the battery after 800 cycles at 0.5C are described in the relevant records of the specific embodiments below, which will not be repeated here.
[0107] An embodiment of the present invention also provides a method for preparing the above-mentioned battery, comprising the following steps: placing a battery cell in a shell, adding an electrolyte thereto, to obtain a battery precursor; placing the battery precursor in a magnetic field for magnetic field induction treatment, to obtain a battery; wherein the battery cell includes a positive electrode sheet, a separator and a negative electrode sheet, and the electrolyte includes the above-mentioned electrolyte or an electrolyte prepared according to the above-mentioned electrolyte preparation method.
[0108] Through the preparation process of the above-mentioned battery, the internal resistance of the prepared battery can be reduced, and the battery's cycle life and other performance can be improved. The reason for this is that the electrolyte contains the above-mentioned magnetic additives, which can coordinate with active ions such as lithium ions to form solvated ions. During the magnetic field induction treatment of the battery precursor, the magnetic field can be used to induce the movement of solvated ions, thereby increasing the ion diffusion rate and the electrolyte's wetting ability on the battery cell, thereby reducing the battery's internal resistance and improving the battery's cycle life and other performance.
[0109] In some embodiments, the magnetic field direction (magnetic potential line direction) of the magnetic field can be basically parallel to the thickness direction of the battery cell, that is, the magnetic field direction is basically parallel to the stacking direction of the positive electrode sheet, the diaphragm and the negative electrode sheet, that is, the magnetic field direction is basically perpendicular to the surface of the positive electrode sheet with the positive electrode coating and the surface of the negative electrode sheet with the negative electrode coating, which is beneficial to the diffusion of solvated ions formed by the coordination of magnetic additives and active ions in the stacking direction of the positive electrode sheet, the diaphragm and the negative electrode sheet, further improving the ion diffusion rate and the wetting ability of the electrolyte to the battery cell, reducing the internal resistance of the battery, and improving the battery's cycle life and other performance.
[0110] In some embodiments, the magnetic field strength of the magnetic field can be 0.1T~0.5T, for example, 0.1T, 0.2T, 0.3T, 0.4T, 0.5T or a range consisting of any two of them, which is beneficial to reduce the internal resistance of the battery and improve the cycle life of the battery and other performance.
[0111] Specifically, the preparation method of the battery also includes the process of aging, forming and aging the battery precursor, and the aging, forming and aging process can be carried out in the process of placing the battery precursor in a magnetic field for magnetic field induction treatment. Specifically, the process of aging, forming and aging the battery precursor can be carried out in a magnetic field. At this time, the magnetic field induction treatment of the battery precursor is completed while the battery precursor is aging, forming and aging.
[0112] In an embodiment of the present invention, the magnetic field can be provided by conventionally applying a magnetic field, for example, a first magnetic field device having a magnetic field generator is used to perform magnetic field induction treatment on the battery precursor, that is, the battery precursor is placed in the first magnetic field device, and a magnetic field is generated by the magnetic field generator, thereby achieving magnetic field induction treatment of the battery precursor.
[0113] In a specific implementation, the positive electrode sheet, the separator and the negative electrode sheet can be assembled into a battery cell by conventional methods in the art, for example, the positive electrode sheet, the separator and the negative electrode sheet are stacked to obtain a stacked battery cell; then the battery cell is placed in a shell, and the liquid injection port is retained, and the electrolyte is injected into it through the liquid injection port (i.e., liquid injection), and then the liquid injection port is closed (sealed) to obtain a battery precursor; then the battery precursor is placed in a first magnetic field device having a magnetic field, and aging (standing), formation and aging treatments are performed in the first magnetic field device in sequence, and at the same time, a magnetic field induction treatment of the battery precursor is completed in the first magnetic field device; after the above treatment is completed, the battery precursor is taken out from the first magnetic field device, and after subsequent processes such as capacity division, a battery is obtained.
[0114] In some embodiments, the time of magnetic field induction treatment (ie, the time the battery precursor is placed in the magnetic field) can be 56 to 66 hours, for example, 56 hours, 58 hours, 60 hours, 62 hours, 64 hours, 66 hours, or a range consisting of any two of them.
[0115] In the embodiments of the present invention, except for the magnetic field induction treatment of the battery precursor, the processes involved, such as liquid injection, sealing, aging, formation, aging treatment, and capacity separation, are all conventional battery assembly processes in the art and are not particularly limited thereto.
[0116] In some embodiments, the aging temperature may be in the range of 40°C to 50°C, such as 40°C, 43°C, 45°C, 48°C, 50°C, or any two thereof.
[0117] In some embodiments, the aging time can be 20 h to 30 h, for example, 20 h, 23 h, 25 h, 28 h, 30 h or a range consisting of any two thereof.
[0118] Generally, after the battery precursor is aged, the aged battery precursor is formed. During the formation process, the aged battery precursor is fully charged (ie, charged to a fully charged state) and then subjected to aging treatment.
[0119] In some embodiments, the formation temperature may be 20° C. to 50° C., such as 20° C., 23° C., 25° C., 28° C., 30° C., or any two thereof. In specific implementations, the formation may be performed at room temperature (normal temperature).
[0120] In some embodiments, the formation process may include: at a formation temperature (such as room temperature), charging the aged battery precursor at a constant current rate of 0.05C for 3 hours, leaving it for 10 minutes, and then charging it at a constant current and voltage rate of 0.2C, with a cut-off voltage of 4V and a cut-off current of 0.01C (at this time, the battery precursor is charged to a fully charged state).
[0121] In some embodiments, the temperature of the aging treatment may be in the range of 40°C to 50°C, such as 40°C, 43°C, 45°C, 48°C, 50°C or any two thereof.
[0122] In some embodiments, the aging treatment time can be 20 h to 30 h, for example, 20 h, 23 h, 25 h, 28 h, 30 h or a range consisting of any two thereof.
[0123] An embodiment of the present invention further provides an electrical device, including the above-mentioned battery or a battery manufactured according to the above-mentioned battery manufacturing method. The electrical device has the corresponding advantages of the above-mentioned battery, which will not be described in detail.
[0124] The electrical equipment in the embodiment of the present invention may be conventional electrical equipment in the art, for example, power equipment such as electric vehicles, etc., and there is no particular limitation on this.
[0125] In some embodiments, the electrical equipment may include a second magnetic field device for applying a magnetic field to a battery. By applying a magnetic field to the battery, the battery is charged and discharged in the magnetic field. The magnetic field can be used to induce the movement of solvated ions formed by the coordination of magnetic additives and active ions such as lithium ions in the electrolyte, thereby increasing the ion diffusion rate, reducing battery impedance, and improving the battery's cycle life and other properties, thereby improving the service life and other properties of the electrical equipment.
[0126] In an embodiment of the present invention, the second magnetic field device may be a conventional device capable of applying a magnetic field. For example, the second magnetic field device has a cavity for accommodating a battery, and the battery is placed in the cavity; the second magnetic field device may be provided with a magnetic field generator for generating a magnetic field, and the magnetic field generator is used to generate a magnetic field to achieve application of a magnetic field to the battery.
[0127] In the embodiments of the present invention, unless otherwise specified, components such as the magnetic field generator are conventional components in the art that can realize their functions and can be connected or assembled into corresponding devices by conventional methods, without any particular limitation.
[0128] In an embodiment of the present invention, the composition and other characteristics of the magnetic additive in the electrolyte can be detected by X-ray photoelectron spectroscopy (XPS) analysis, X-ray diffraction (XRD) analysis, infrared spectroscopy analysis, etc. For example, the composition of the functionalized modification layer of the magnetic additive (for example, detecting the organic matrix material and the functional groups contained therein) and other characteristics can be detected by infrared spectroscopy testing, etc.
[0129] In the embodiment of the present invention, the thickness of the functionalized modified layer in the magnetic additive and other characteristics can be measured by a transmission electron microscope (TEM). It can be understood that the thickness of the functionalized modified layer of the magnetic additive is an average thickness. In specific implementation, the thickness of the functionalized modified layer of at least 20 magnetic additive particles in the field of view can be tested by TEM (specifically, the thickness of the functionalized modified layer of 100 magnetic additive particles in the field of view can be tested), and the average value is taken as the final measurement result.
[0130] In specific implementation, the battery can be disassembled to obtain the electrolyte, and the magnetic additive can be taken out from the electrolyte (specifically, the electrolyte can be dried to obtain a granular product which is the magnetic additive, or the magnetic additive can be sucked out of the electrolyte by magnetic attraction or the like), and the magnetic additive can be washed with water and ethanol in sequence, specifically, washed with water three times, then washed with ethanol three times, and then dried, specifically, dried at 60°C to 80°C, and then the magnetic additive can be subjected to the above-mentioned XPS, XRD, infrared spectroscopy, TEM and other analyses to determine the composition of the magnetic additive and the thickness of the functionalized modification layer and other characteristics.
[0131] The present invention is further described below through specific embodiments.
[0132] Example 1
[0133] 1. Preparation of magnetic additives
[0134] Under an inert atmosphere, FeCl3.6H2O and FeCl2.4H2O were dissolved in 100 mL of water at a molar ratio of 2:1, and an ammonia solution was slowly added thereto until the pH value of the resulting solution was about 10. After reacting for 3 h, magnetic separation was performed, and then Fe3O4 nanoparticles were obtained by washing and drying.
[0135] Under an inert atmosphere, 0.5 g of Fe3O4 nanoparticles were dispersed in 100 mL of a mixed solvent of ethanol and water (the volume ratio of ethanol to water was 1:1), 1 mL of APTES was added thereto, and then the mixture was reacted at 25°C for 6 h (i.e., the silanization reaction temperature was 25°C and the silanization reaction time was 6 h); after the reaction, the reaction system was centrifuged, and the obtained solid product was washed with water 3 times and then washed with anhydrous ethanol 3 times to remove the unreacted silanization agent, thereby obtaining silane-modified magnetic nanoparticles (i.e., Fe3O4 nanoparticles after surface treatment);
[0136] The silane-modified magnetic nanoparticles and 0.6 g of trimethylacetyl chloride were dissolved in 100 mL of THF, placed in an inert atmosphere, and reacted at 25°C for 3 h (i.e., the functionalization modification temperature was 25°C and the functionalization modification time was 3 h) to obtain a magnetic additive (i.e., Fe3O4 nanoparticles with a functionalized modification layer on the surface).
[0137] 2. Preparation of electrolyte
[0138] EC, EMC, DMC and LiPF6 are mixed, and a magnetic additive is added thereto, and the mixture is stirred at a constant temperature of 25°C for 2 hours to obtain an electrolyte; wherein the mass ratio of EC, EMC and DMC is 1:1:1, the mass percentage of LiPF6 in the electrolyte is 12%, and the mass percentage of the magnetic additive in the electrolyte is 0.01%.
[0139] 3. Preparation of batteries
[0140] (1) Preparation of positive electrode
[0141] Lithium iron phosphate, carbon black and PVDF were mixed in a mass ratio of 100:0.8:2.3, and NMP was added and stirred evenly to prepare a positive electrode slurry;
[0142] The positive electrode slurry is coated on the front and back surfaces of the aluminum foil, and after drying and rolling, a positive electrode coating is formed on the front and back surfaces of the aluminum foil to obtain a positive electrode sheet.
[0143] (2) Preparation of negative electrode
[0144] Graphite, carbon black, SBR, and CMC were mixed in a mass ratio of 100:0.8:1.5:1.7, and deionized water was added and stirred evenly to prepare a negative electrode slurry;
[0145] The negative electrode slurry is coated on the front and back surfaces of the copper foil, and after drying and rolling, a negative electrode coating is formed on the front and back surfaces of the copper foil to obtain a negative electrode sheet.
[0146] (3) Battery assembly
[0147] The positive electrode sheet, the separator (PP film) and the negative electrode sheet are alternately stacked to form a stacked battery cell;
[0148] Placing the laminated battery core in an aluminum-plastic film and retaining a liquid injection port, injecting the above-mentioned electrolyte into the film through the liquid injection port, and then sealing the liquid injection port to obtain a battery precursor;
[0149] The battery precursor is placed in a magnetic field, and subjected to aging, formation and aging treatments in sequence in the magnetic field, while achieving magnetic field induction treatment of the battery precursor; the battery precursor is then taken out of the magnetic field, and after processes such as capacity division, a soft-pack lithium-ion battery is obtained.
[0150] The aging temperature is 45°C and the aging time is 24h.
[0151] The formation process is as follows: at 25°C, the aged battery precursor is charged at a constant current of 0.05C for 3 hours, left for 10 minutes, and then charged at a constant current and voltage of 0.2C, with a cut-off voltage of 4V and a cut-off current of 0.01C.
[0152] The aging treatment temperature is 45°C and the aging treatment time is 24h.
[0153] The magnetic field induction treatment time is about 60 hours.
[0154] Examples 2 to 19, Examples 21 to 24: The difference from Example 1 is that the conditions in the preparation process of the magnetic additive (type of silane coupling agent, silanization reaction temperature, silanization reaction time, type of functional modifier, functionalization modification temperature, functionalization modification time), the thickness of the functionalized modification layer in the magnetic additive, the stirring time in the preparation process of the electrolyte, the mass percentage of the magnetic additive in the electrolyte, the magnetic field strength and other conditions are different, see Tables 1 and 2 for details. Except for the differences shown in Tables 1 and 2, the other conditions are the same as in Example 1.
[0155] The difference between Example 7 and Example 1 is that the magnetic additive is magnetic nanoparticles (Fe3O4 nanoparticles), and no functional modification layer is formed on the surface thereof. The other conditions are the same as those in Example 1.
[0156] Among them, the difference between Example 23 and Example 1 is that the magnetic additive is silane-modified magnetic nanoparticles, and the silane-modified magnetic nanoparticles are not reacted with the functional modifier (that is, the magnetic additive in Example 23 is obtained by subjecting the magnetic nanoparticles (Fe3O4 nanoparticles) to a first silane modification treatment using a first silane coupling agent (APTES), and the other conditions are the same as in Example 1.
[0157] Comparative Example 1: The difference from Example 1 is that no magnetic additive is added to the electrolyte, and the other conditions are the same as those of Example 1.
[0158] Comparative Example 2: The difference from Example 1 is that no magnetic additive is added to the electrolyte, and the aging, formation and aging treatment processes of the battery precursor are not carried out in a magnetic field (that is, no magnetic field is applied to the battery precursor), and the other conditions are the same as in Example 1.
[0159] The performance of the soft-pack lithium-ion batteries of Examples 1 to 19, Examples 21 to 24 and Comparative Examples 1 to 2 was tested by the following process, and the results are shown in Table 2:
[0160] (1) Cycle performance (25°C, 0.5C cycle 800 cycles capacity retention rate) test: At 45°C, the soft-pack lithium-ion battery was charged to 3.8V at 0.5C constant current and left for 10 minutes; then discharged to 2.0V at 0.5C constant current and left for 10 minutes, and cycled 1000 times; capacity retention rate = (C 1000 / C1)×100%, C1 is the discharge capacity of one cycle, C 1000 is the discharge capacity after 1000 cycles.
[0161] (2) Battery internal resistance (50% SOC charging DCIR) test: After the soft-pack lithium-ion battery is discharged to 2.0V at 1 / 3C, it is charged to 50% SOC at 1 / 3C and placed at 25°C for another 2h, and the voltage value U1 is recorded; the battery is discharged at 1.5C for 30s, and the voltage value U2 is recorded; placed for 1h, charged at 0.1C for 450s, and placed for 1h; then the 50% SOC charging DCIR = (U1-U2) / I.
[0162] (3) Battery fast charging performance (fast charging time) test: Place the soft-pack lithium-ion battery in a 25°C constant temperature box and let it stand for 30 minutes. Charge the soft-pack lithium-ion battery at a constant current of 3C to a voltage of 3.6V, then charge it at a constant current of 1C to 3.8V, and then charge it at a constant voltage to a current of 0.05C. The charging time of this process is the fast charging time (see Table 2). The fast charging performance of the lithium-ion battery is evaluated by the fast charging time of the soft-pack lithium-ion battery. The longer the fast charging time, the worse the fast charging performance, and the shorter the fast charging time, the better the fast charging performance.
[0163] Example 20: The difference from Example 1 is that: (1) the aging, formation and aging treatment processes of the battery precursor are not carried out in a magnetic field; (2) the prepared soft-pack lithium-ion battery is subjected to the above-mentioned cycle performance test, DCIR test and fast charging performance test in a magnetic field with a magnetic field strength of 0.1 T. The results are shown in Table 2; the other conditions are the same as in Example 1.
[0164] Table 1
[0165]
[0166] Table 2
[0167]
[0168] It can be seen from Table 2 that, relative to Comparative Examples 1 and 2, the introduction of magnetic additives into the electrolytes of Examples 1 to 24 can reduce the internal resistance of the battery, shorten the fast charging time of the battery, and improve the cycle capacity retention rate of the battery.
[0169] Among them, relative to Example 6, in Examples 1 to 5, the mass percentage of the magnetic additive in the electrolyte is in the range of 0.01% to 3%, which is beneficial to further reduce the internal resistance of the battery and improve the cycle capacity retention rate of the battery.
[0170] In addition, relative to Example 7, in Examples 1 to 6 and Examples 8 to 24, the magnetic additive includes magnetic nanoparticles and a functionalized modification layer present on the surface of the magnetic nanoparticles, which is beneficial to further reduce the internal resistance of the battery, shorten the fast charging time, and improve the battery's cycle capacity retention rate.
[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a battery, characterized in that: The following steps are involved: Placing the battery cell in a shell and adding an electrolyte therein to prepare a battery precursor; Placing the battery precursor in a magnetic field for magnetic field induction treatment to obtain the battery; The battery core comprises a positive electrode sheet, a separator and a negative electrode sheet, the electrolyte comprises a magnetic additive, the magnetic additive comprises magnetic nanoparticles and a functional modification layer present on the surface of the magnetic nanoparticles, the functional modification layer comprises an organic matrix material containing oxygen and / or nitrogen elements; the thickness of the functional modification layer is 2nm~10nm.
2. The method for preparing a battery according to claim 1, characterized in that: The organic matrix material contains one or more of a carboxyl group, an ether group, a carbonyl group, an amino group, and a pyridyl group.
3. The method for preparing a battery according to claim 1, characterized in that: The magnetic nanoparticles include one or more of magnetic metal oxide nanoparticles, metal nanoparticles, and alloy nanoparticles.
4. The method for preparing a battery according to claim 3, characterized in that: The magnetic metal oxide nanoparticles include ferroferric oxide nanoparticles, the metal nanoparticles include one or more of cobalt nanoparticles, nickel nanoparticles and iron nanoparticles, and the alloy nanoparticles include iron-cobalt alloy nanoparticles and / or iron-nickel alloy nanoparticles.
5. The method for preparing a battery according to claim 1, characterized in that: The mass percentage of the magnetic additive in the electrolyte is 0.01% to 3%.
6. The method for preparing a battery according to any one of claims 1 to 5, characterized in that: The electrolyte further includes a first solvent, the first solvent includes an organic solvent, and the organic solvent includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate; And / or, the electrolyte further includes a lithium salt, and the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(fluorosulfonyl)imide.
7. The method for preparing a battery according to any one of claims 1 to 5, characterized in that: The electrolyte is prepared according to a process comprising the following steps: mixing the magnetic additive, a first solvent, and an electrolyte salt to obtain the electrolyte.
8. The method for preparing a battery according to claim 7, characterized in that: The step of mixing the magnetic additive, the first solvent and the electrolyte salt to obtain the electrolyte solution specifically comprises: mixing the magnetic additive, the first solvent and the electrolyte salt, and stirring for 2 hours to 8 hours to obtain the electrolyte solution.
9. The method for preparing a battery according to claim 7, characterized in that: The preparation process of the magnetic additive includes: using a first silane coupling agent containing oxygen and / or nitrogen elements to perform a first silane modification treatment on magnetic nanoparticles to form a functionalized modification layer on the surface of the magnetic nanoparticles to obtain the magnetic additive.
10. The method for preparing a battery according to claim 9, characterized in that: The temperature of the first silane modification treatment is 25°C to 80°C, and the time is 6h to 12h; And / or, the first silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethylsilane, 3-aminopropyltriethylsilane, and (3-trimethoxysilylpropyl)-4-pyridine.
11. The method for preparing a battery according to claim 7, characterized in that: The preparation process of the magnetic additive comprises: Using a second silane coupling agent to perform a second silane modification treatment on the magnetic nanoparticles to obtain silane-modified magnetic nanoparticles; The silane-modified magnetic nanoparticles are reacted with a functional modifier to form a functionalized modification layer on the surface of the magnetic nanoparticles to obtain the magnetic additive; wherein at least one of the second silane coupling agent and the functional modifier includes an organic compound containing oxygen and / or nitrogen.
12. The method for preparing a battery according to claim 11, characterized in that: The temperature of the second silane modification treatment is 25°C to 80°C, and the time is 6h to 12h; And / or, the conditions for the reaction of the silane-modified magnetic nanoparticles and the functional modifier are: the reaction temperature is 25° C. to 80° C., and the reaction time is 3 h to 12 h; and / or, the functional modifier includes one or more of succinic anhydride, ethylene oxide, trimethylacetyl chloride, and pyridine; And / or, the second silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, (3-chloropropyl)trimethoxysilane, (3-iodopropyl)trimethoxysilane, trichlorosilane, 3-aminopropyltrimethylsilane, and 3-aminopropyltriethylsilane.
13. The method for preparing a battery according to any one of claims 1 to 5, characterized in that: The magnetic field strength of the magnetic field is 0.1T~0.5T; And / or, the magnetic field direction of the magnetic field is parallel to the thickness direction of the battery core; And / or, the preparation method of the battery also includes the process of subjecting the battery precursor to aging, formation and aging treatment, and the aging, formation and aging treatment processes are performed during the process of placing the battery precursor in a magnetic field for magnetic field induction treatment.
14. The method for preparing a battery according to any one of claims 1 to 5, characterized in that: The battery is a lithium-ion battery.
15. An electrical equipment, characterized in that: A battery prepared by the method for preparing a battery according to any one of claims 1 to 14.
16. The electrical equipment according to claim 15, characterized in that: The electric device further comprises a second magnetic field device for applying a magnetic field to the battery.
Citation Information
Patent Citations
Electrolyte additive and preparation method and application thereof
CN115799676A
Low-temperature-resistant lithium battery
CN116470121A
Magnetic nanofluid electrolyte and application thereof
CN117790856A
Electrolyte for convection-induction type secondary battery and secondary battery comprising same
WO2022182132A1